DETERMINAN EKSPOR KOMODITI UNGGULAN INDONESIA KE UNI EMIRAT ARAB - Faizal Amir; Wiwi Uliyati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
United Arab Emirates is one of the non-traditional export markets of Indonesia. Trade between Indonesia and United Arab Emirates is expected can open up trade and investment opportunities are greater for the two countries. This study was conducted to analyze the competitiveness, degree of integration, and determinants of trade flows Indonesian main export commodities to the United Arab Emirates in the period 2009-2013. The results showed that the Indonesian main export commodities both in agriculture and manufacturing sectors in United Arab Emirates market have high competitiveness with demonstrated by RCA > 1. The results of the analysis of the degree of integration Indonesian main export commodities as a whole shows that the intra-industry trade (IIT) between Indonesia and United Arab Emirates in general is on the degree of integration in one direction (no integration). The results of the estimation export demand function, Indonesian main export commodities to the United Arab Emirates the agricultural sector mode has five independent variables that significantly influence of the Indonesian main export commodities to the United Arab Emirates, Indonesian export price, export price of competitor countries, United Arab Emirates real GDP, real exchange rate, and NTM dummy. On the model of the manufacturing sector, there are four independent variables that significantly influence of the export, Indonesian export price, export price of competitor countries, United Arab Emirates real GDP and real exchange rate